2016
DOI: 10.3390/ijms17050667
|View full text |Cite
|
Sign up to set email alerts
|

The Establishment of an Assay to Measure DNA Polymerase-Catalyzed Repair of UVB-Induced DNA Damage in Skin Cells and Screening of DNA Polymerase Enhancers from Medicinal Plants

Abstract: An in vitro assay method was established to measure the activity of cellular DNA polymerases (Pols) in cultured normal human epidermal keratinocytes (NHEKs) by modifying Pol inhibitor activity. Ultraviolet (UV) irradiation enhanced the activity of Pols, especially DNA repair-related Pols, in the cell extracts of NHEKs. The optimal ultraviolet B (UVB) exposure dose and culture time to upregulate Pols activity was 100 mJ/cm2 and 4-h incubation, respectively. We screened eight extracts of medicinal plants for enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For example, DNA damage can be prevented by certain molecules, especially natural antioxidant compounds such as flavonoids, polyphenols, and carotenoids, which exist in fruits, vegetables, and medicinal plants. [17][18][19][20][21][22] Screening for highly effective, non-toxic, antioxidant compounds that protect against DNA damage is now an active area of biomedical research [23] , and interest in this area is growing. Various natural antioxidants have been successfully isolated from plants, such as rutin, resveratrol, and various flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DNA damage can be prevented by certain molecules, especially natural antioxidant compounds such as flavonoids, polyphenols, and carotenoids, which exist in fruits, vegetables, and medicinal plants. [17][18][19][20][21][22] Screening for highly effective, non-toxic, antioxidant compounds that protect against DNA damage is now an active area of biomedical research [23] , and interest in this area is growing. Various natural antioxidants have been successfully isolated from plants, such as rutin, resveratrol, and various flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…1 indicate that damaged mitochondria remained in cells at 24 h after exposure to more than 40 mJ/cm 2 of UV-B, suggesting that the dose of UV-B had an impact on mitophagy in NHEKs. Additionally, a previous study 6 indicated that the inherent cellular DNA repair system peaked at 4 h after UV-B irradiation.…”
Section: Mitophagy In Uv-b-irradiated Nheksmentioning
confidence: 93%
“…We assumed that it is effective to enhance the inherent repair ability of cells by promoting activity of cellular pol which synthesizes DNA strands in the repair system. In previous studies 5 , 6 , we established a method for measuring pol activity in UV-B-irradiated normal human epidermal keratinocytes NHEKs , and found that the inherent cellular DNA repair activity peaked at 4 h after irradiation with UV-B in NHEKs. We also showed that Rhodomyrtus tomentosa fruit extract, which has properties to protect epidermal keratinocytes from UV-B-induced apoptosis 7 , enhanced the cellular pol activity and suppressed CPD production.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian cells are known to contain at least 16 different DNA polymerases that function in semiconservative DNA replication (pols α, δ, ε), base excision repair (pol β), mitochondrial DNA replication, repair and degradation (pol γ), DSB repair and immunological diversity (pols λ, μ, pol θ, and terminal deoxynucleotidyl transferase), and DNA damage tolerance by translesion synthesis [ 8 ]. Among them, DNA polymerase theta has the most unique structure.…”
Section: Polθ: Structure and Functionsmentioning
confidence: 99%
“…In recent research, inhibiting Pol was found to sensitize cells to replication stress produced by drugs such as topoisomerase poisons or ATR inhibitors, leading to new cancer treatment candidates. DSB repair-proficient cancer cells expressing high levels of Polθ may be sensitive to the inhibition of Polθ in combination with standard cytotoxic drugs [ 8 ].…”
Section: The Role Of Polθ In Malignant Cellsmentioning
confidence: 99%